Modeling of an energy efficient fan installation based on an adjustable electric drive with a fuzzy logic regulator - Klendiy, P. B.; Fedirko, M. M.; Kamyshlov, V. G.; Podobaylo , V. G.; Dudar, O. P (Energy and Automation, 2025)
Centrifugal fan installations are the most common in various spheres of production, both light and heavy industry. More often, centrifugal fans are installed as unregulated electric drive installations, especially low capacity. But there are a lot of technological equipment, especially in the production sphere, where it is necessary to regulate the productivity of fans. Moreover, regulation is carried out in a fairly wide range. Electrical drive of centrifugal fans is usually realize on the basis of an asynchronous short -circuited engine. To adjust the supply of such fan is carried out the adjusting of the speed rotation of the engine using the frequency converter Among the known ways of regulating the efficiency of fan installations, namely throttling, change of the angle of installation of blades, using of guiding machines, regulating of the number of rotations of the fan shaft is the most effective way. In modern conditions, the change of the fan shaft rotation is carried out by changing the drive shaft rotation of drive engine. In the article is considered the issue of increasing the energy efficiency of fan installations by using an adjustable electrical drive with using the regulator, built on the principles of fuzzy logic. The mathematical model of the system in the Matlab application package has been developed, computer modeling has been carried out and the benefits of the proposed approach are shown in comparing to the traditional methods of regulation. Key words: fan installation, energy efficiency, adjustable electrical drive, asynchronous engine, sub- regulator, fuzzy logic controller, Matlab